The academia we have and the one we want: on the centrality of gender equality. Issue 4 (2nd October 2017) - Munar, Ana María; Khoo-Lattimore, Catheryn; Chambers, Donna; Biran, Avital
Abstract: This concluding essay challenges the tendency in academia to consider feminist epistemologies and gender equality as peripheral when instead they are central to the flourishing of tourism scholarship. We analyse pervasive misconceptions about gender in higher education and present an alternative way of doing academia based on dissent and critical engagement; commitment to democratic practices that allow for different points of view to be shared and accepted as trustworthy; engagement with value judgement in knowledge production; care and accountability in our ways of knowing and teaching; and the establishment of diverse career patterns and decent contractual conditions to researchers so freedom of thought can take place.